A Gender Analysis of Interaction in Online Work Meeting Tools - Ribeiro, Karen da Silva Figueiredo Medeiros (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Synchronous work meetings with geographically distributed teams mediated by technologies have been a practice for decades. The advancement of ICT has allowed the improvement of the technologies used, especially in the last 20 years. However, the 2020' covid 19 health pandemic has expanded this practice and popularized its tools. Although there are work conducts and policies, work meeting are spaces where social interaction can lead to behaviors of harassment and social oppression related to minorities. Some examples are the unwanted interruptions, the theft of protagonism or ideas and the inappropriate comments, especially from a gender perspective. By considering the popularization of the use of systems to support online work meetings, this article aims to execute a gender analysis of interaction via web conferencing and video calling tools, in the context of their use for synchronous work meetings. The gender analysis is based on the qualities of the Feminist HCI theory in order to identify if and how gender differences happen in those interactions. The preliminary survey with 96 people revealed that gender differences are present in those interactions and that they reproduce some known kinds of oppression towards female and non binary people.